Unprecedented stability in Au@Co core-shell bimetallic catalyst supported on SBA-15 (Au@Co/SBA-15) for atmospheric pressure CO hydrogenation - Jain, P.; Chimote, M.; Vinod, C. P. (Materials Today Sustainability, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Bimetallic nanoparticles demonstrating <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/synergistic-effect" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about synergistic effect from ScienceDirect's AI-generated Topic Pages">synergistic effect (electronic or geometric modification) often show distinct chemical and physical properties compared with the parent metals. In catalysis, this provides opportunities to engineer solid materials with appreciable activity, selectivity, and stability. In the present study, we have synthesized Au@Co core–shell bimetallic nanoparticles by colloidal synthesis approach with a focus to study and explore the synergistic effect between Au and Co in Au@Co <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/bimetallic-catalyst" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about bimetallic catalyst from ScienceDirect's AI-generated Topic Pages">bimetallic catalyst supported on SBA-15 on <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/fischer-tropsch" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px; font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;" title="Learn more about Fischer Tropsch from ScienceDirect's AI-generated Topic Pages">Fischer Tropsch<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> (FT) reaction. The deactivation of catalyst is a significant drawback in CO hydrogenation (syngas conversion/FT synthesis), and the present study provides the design of a new material, which resists the surface cobalt oxide formation and inactive coke formation and gives efficient CO conversion with high stability.